Pola Pembelajaran Everyone is a Teacher Here sebagai Alternative Peningkatan Proses Belajar Aktif Peserta Didik - Eva Maghfiroh (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
Efforts to build the Indonesian nation so that the quality of life increases is not an easy and simple matter. Among the big challenges facing this nation is the challenge of education in its broadest sense. One of them is the environment which also colors, influences human growth and development. An education is said to be a process to mature humans. Or in other words education is an attempt to humanize humans. Education is in an important aspect of life, it is closely related to successors whose future must be well prepared, and all of which can only be achieved by education. The everyone is a teacher here method is an easy strategy to obtain large class participation and the responsibility of students. In learning activities, and not necessarily all from the teacher, students just sit in silence and listen to the lessons the teacher delivers, but students can describe and understand each other.